PENERAPAN PEMBELAJARAN KOOPERATIF METODE LINGKARAN DALAM LINGKARAN LUAR TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMP NEGERI 11 PADANG - Rahmi, Rahmi; Putri, Anggun Leo (Prodi Pendidikan Matematika, 2013)
TheÂ  purposeÂ  ofÂ  thisÂ  researchÂ  isÂ  toÂ  knowÂ  whetherÂ  studentsâÂ  understandingÂ  of mathematicsÂ  conceptÂ  byÂ  usingÂ  Inside-OutsideÂ  CircleÂ  methodÂ  isÂ  betterÂ  thanÂ  studentsâ understandingÂ  ofÂ  mathematicsÂ  conceptÂ  byÂ  using conventional Â methodÂ  forÂ  student Â garade VIII of SMPN 11 Padang. The kind of this research is experimentalresearch, by using students in class VIII D and VIII E as samples which registered in 2011-2012 Â academic year. The instrument of this research is written test in essay form based on Â the indicator of concept understanding. Â Based on the data analysis to test the hypothesis, it is found that P-value 0.013 Â is lower thanÂ  Î±=0.05, it means that Hois rejected and H1is accepted. So, it can be Â concludedÂ  thatÂ  studentsâÂ  understandingÂ  ofÂ  mathematicsÂ  conceptÂ  byÂ  usingÂ  InsideOutside Circle method is better than studentsâ understanding of mathematics concept Â by using conventional method.Key Word: Lingkaran Dalam Lingkaran Luar, Pemahaman Konsep Matematis